Branes in string theory - Sorokin, D.P. (Вопросы атомной науки и техники, 2007)
We give a simple overview of some basic aspects of the dynamics of branes in string theory and of their role in the attempts to get from String Theory a realistic model of fundamental interactions of elementary particles.